2008
DOI: 10.1073/pnas.0708092105
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β is an essential mediator of the antineurogenic and anhedonic effects of stress

Abstract: Stress decreases neurogenesis in the adult hippocampus, and blockade of this effect is required for the actions of antidepressants in behavioral models of depression. However, the mechanisms underlying these effects of stress have not been identified. Here, we demonstrate an essential role for the proinflammatory cytokine IL-1␤. Administration of IL-1␤ or acute stress suppressed hippocampal cell proliferation. Blockade of the IL-1␤ receptor, IL-1RI, by using either an inhibitor or IL-1RI null mice blocks the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
577
3
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 775 publications
(612 citation statements)
references
References 55 publications
27
577
3
5
Order By: Relevance
“…IkK activity in the hippocampus has also been found to affect histone acteylation, and this action was shown to be a critical regulator of reconsolidation of conditioned fear memories (Lubin and Sweatt, 2007). Interestingly, activation of NFkB in the hippocampus by IL-1b has been shown to inhibit neurogenesis and is important in the pro-depressant effects of chronic unpredictable stress (Koo and Duman, 2008;Koo et al, 2010). Complementary to our findings, Koo et al (2010) found that inhibition of NFkB in hippocampus blocked the anhedonic effects of CUS as measured by sucrose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…IkK activity in the hippocampus has also been found to affect histone acteylation, and this action was shown to be a critical regulator of reconsolidation of conditioned fear memories (Lubin and Sweatt, 2007). Interestingly, activation of NFkB in the hippocampus by IL-1b has been shown to inhibit neurogenesis and is important in the pro-depressant effects of chronic unpredictable stress (Koo and Duman, 2008;Koo et al, 2010). Complementary to our findings, Koo et al (2010) found that inhibition of NFkB in hippocampus blocked the anhedonic effects of CUS as measured by sucrose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to IFN-a's effects on serotonin , dopamine (Felger et al, 2007), glutamate (Raison et al, 2010b), and the hypothalamic-pituitary-adrenal axis (Raison et al, 2010a), a decrease in BDNF may ultimately be the reason for the development of depression during IFN-a treatment. Related to this, social isolation decreases central BDNF, an effect which is likely mediated by the inflammatory cytokine IL1b (Barrientos et al, 2003;Ben Menachem-Zidon et al, 2008;Koo and Duman, 2008). IFN-a also appears to decrease cell proliferation in the hippocampus via increased IL-1b (Kaneko et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that IL-1β is antineurogenic (Koo and Duman, 2008;Ryan et al, 2013) by activation of the tumor suppressor p53 (Guadagno et al, 2015) or via adrenocortical activation (Goshen et al, 2008). Other findings suggest a proneurogenic effect of IL-1β (de la Mano et al, 2007;Xue et al, 2015).…”
mentioning
confidence: 99%